2015
DOI: 10.1089/ars.2014.6103
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic-Mediated Reprogramming of Pancreatic Endocrine Cells

Abstract: Epigenetic-mediated regulation of transcription factor binding in pancreatic α-cells by specific drugs to direct reprogramming into functional insulin producing cells could be of potential innovative therapy for the treatment of T1D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 117 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…A key challenge to understand the physiological role of Set7 is characterizing the regulatory function during development: in the skeletal muscle example described previously, differentiation occurs by Set7 mediated activation (40). Other studies have shown tissue-specific activation of the Set7 gene during β-cell development is dependent on the (pancreatic and duodenal homeobox 1) PDX1 transcription factor (45) with the capacity to reprogram endocrine cells (46). Studies investigating p53-dependant transcriptional regulation show the homozygous knockout of the Set7 allele in mice are viable, which is at odds with an earlier study (44), without causing marked consequences on tumor suppressor activity (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…A key challenge to understand the physiological role of Set7 is characterizing the regulatory function during development: in the skeletal muscle example described previously, differentiation occurs by Set7 mediated activation (40). Other studies have shown tissue-specific activation of the Set7 gene during β-cell development is dependent on the (pancreatic and duodenal homeobox 1) PDX1 transcription factor (45) with the capacity to reprogram endocrine cells (46). Studies investigating p53-dependant transcriptional regulation show the homozygous knockout of the Set7 allele in mice are viable, which is at odds with an earlier study (44), without causing marked consequences on tumor suppressor activity (47,48).…”
Section: Discussionmentioning
confidence: 99%